Suppression of Electrochemically Driven Phase Transitions in Nanostructured MoS2 Pseudocapacitors Probed Using Operando X-ray Diffraction - Cook, John B.; Lin, Terri C.; Kim, Hyung-Seok; Siordia, Andrew; Dunn, Bruce S.; Tolbert, Sarah H. (AMER CHEMICAL SOC, 2019)
Pseudocapacitors with nondiffusion-limited charge storage mechanisms allow for fast kinetics that exceed conventional battery materials. It has been demonstrated that nanostructuring conventional battery materials can induce pseudocapacitive behavior. In our previous study, we found that assemblies of metallic 1T MoS2 nanocrystals show faster charge storage compared to the bulk material. Quantitative electrochemistry demonstrated that the current response is capacitive. In this work, we perform a series of operando X-ray diffraction studies upon electrochemical cycling to show that the high capacitive response of metallic 1T MoS2 nanocrystals is due to suppression of the standard first-order phase transition. In bulk MoS2, a phase transition between 1T and triclinic phases (LixMoS2) is observed during lithiation and delithiation in both the galvanostatic traces (as distinctive plateaus) and the X-ray diffraction patterns with the appearance of the additional peaks. MoS2 nanocrystal assemblies, on the other hand, show none of these features. We hypothesize that the reduced MoS2 crystallite size suppresses the first-order phase transition and gives rise to solid solution-like behavior, potentially due to the unfavorable formation of nucleation sites in confined spaces. Overall, we find that nanostructuring MoS2 suppresses the 1T-triclinic phase transition and shortens Li-ion diffusion path lengths, allowing MoS2 nanocrystal assemblies to behave as nearly ideal pseudocapacitors.
Keywords: LITHIUM INTERCALATION; ATOMIC MECHANISM; LI-INTERCALATION; ENERGY-STORAGE; NANOSHEETS; TRANSFORMATION; DYNAMICS; SIZE; CRYSTALLITES; EVOLUTION